Lasiodiplodia iraniensis, a New Causal Agent of Tuber Rot on Yam (Dioscorea Species) Imported into the United States and Implications for Quarantine Decisions - Jibrin, Mustafa Ojonuba (Plant disease, 2022)
One negative consequence of international trade of agricultural commodities is the inadvertent global spread of crop diseases. Yam (Dioscorea spp.) is a staple food crop in many countries and is traded globally. Most of the commercially traded yams in the United States are imported. In late 2020, samples of yam tubers from a commercial facility were submitted to the plant diagnostic clinic at the UF/IFAS Tropical Research and Education Center in Homestead, Florida. Samples showed rotten symptoms and were drawn from lots that were marked to be destroyed because the source of the rotting symptoms was unknown. Preliminary isolation showed that a fungus was consistently associated with the symptoms and was confirmed in the subsequent pathogenicity test as the causal agent. The fungus grew profusely on potato dextrose agar (PDA) with highly melanized hyphae. Matured conidia showed longitudinal striations. Based on its growth pattern and morphology, it was suspected that this fungus may be in the genus Lasiodiplodia. DNA-based identification using partial sequences of the internal transcribed spacer (ITS), β-tubulin (TUB2), 28S rDNA (LSU), and elongation factor alpha (EF1-α) genes confirmed the identity of the isolates as Lasiodiplodia iraniensis Abdollahz., Zare & A.J.L. Phillips (synonym: L. iranensis). This is the first report of L. iraniensis affecting yam and has implications for international trade. This finding will provide an important foundation for making quarantine decisions to prevent spread of this disease